An analysis of paper made from the dung of elephant, rhinoceros and other wild herbivores to develop conservation guidelines - Loubser, Maggi (University of Pretoria, 2023)
Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2022.